Pengembangan Kapasitas Mahasiswa Menuju Generasi Unggul di Era 4.0 - Ansar Suherman; Herman Lawelai; Nurtang Nurtang; Nabila Salam; Ahmad Muhardin Hadmar (Society : Jurnal Pengabdian Masyarakat, 2022)
The purpose of this community service is to face the Industrial Revolution 4.0, every individual, especially students, seeks to master the talents or skills needed to give birth to a professional workforce that can adapt to current conditions. To be able to adapt to the Industrial Revolution 4.0, a student must have qualities that machines do not have. One example is the ability to solve problems or creativity, and soft skills are very important for a student to have. The result of community service is that students are equipped with competencies such as complex problem solving, critical thinking, creativity, management, coordination with others, emotional intelligence, judgment, and decision making, service orientation, negotiation, and cognitive flexibility needed to meet future developments. In addition, students who already have expertise must continue to improve their abilities, while those who currently have skills but are no longer relevant must immediately adjust their skills to meet current market demands.